Discourse markers (DMs) in classroom oral presentation of Arab postgraduate students - Alkhawaja, Hussein W.; Paramasivam, Shamala; Nimehchisalem, Vahid; Mohd Kasim, Zalina (Macrothink Institute, 2022)
Towards auto didacticism in the learning of English language in Malaysian universities, students are required to do oral presentations as an academic task such as presentations of articles reviews, book chapter summaries and mini or final project proposals. To conduct these classroom oral presentations, students usually employ a number of technological aids and resources such as computers, overhead projectors and Microsoft PowerPoint software to create their slides. In fact, conducting coherent oral presentations goes beyond the use of technology to include appropriate use of linguistic devices called discourse markers. However, the absence or misuse of these markers in oral presentation would not only affect the flow of the ideas, coherence of speech and organization of facts but might also alter the intended message of the presenter. The objective of this study was to shed light on the use of these markers by focusing on the types and functions of these markers. For this purpose, a discourse analysis approach was used in which the data were collected in the form of audio-recordings of students’ oral presentations, and then analyzed based on Fraser’s (2009) classification and functions of discourse markers. The findings of this study are useful for instruction of better oral presentation performance of ESL/EFL learners in general and postgraduate students in particular. They also add to the current body of literature in the area of discourse studies.